2018
DOI: 10.1097/pas.0000000000001036
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Features of Gastrointestinal Tract Biopsies in IgA Vasculitis (Henoch-Schönlein Purpura)

Abstract: Immunoglobulin A (IgA) vasculitis or Henoch-Schönlein purpura (HSP) typically occurs in the pediatric population, although rare cases also occur in adults. Gastrointestinal (GI) involvement is common. The "classic" histologic finding in IgA vasculitis (HSP) is leukocytoclastic vasculitis (LCV); other histologic features in biopsies of IgA vasculitis (HSP) have only been rarely described. The pathology archival files at our institution were searched for GI biopsies from patients with IgA vasculitis (HSP). Slide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…It also revealed active inflammation with eosinophilic component. The presence of an eosinophilic infiltrate in HSP duodenitis was also described by Louie et al in three of the 16 duodenal biopsies of HSP patients ( 13 ).…”
Section: Discussionsupporting
confidence: 65%
“…It also revealed active inflammation with eosinophilic component. The presence of an eosinophilic infiltrate in HSP duodenitis was also described by Louie et al in three of the 16 duodenal biopsies of HSP patients ( 13 ).…”
Section: Discussionsupporting
confidence: 65%
“…IgA expression not only in the lamina propria immune cells but also in the capillary vessel walls (figure 2C) led us to consider the possibility of enteric IgA vasculitis as IgA deposition in capillary walls is a specific finding of this immune disorder. 10 A significant decrease in serum factor XIII activity was also consistent with IgA vasculitis. Thus, this patient was diagnosed with solitary enteric IgA vasculitis and then treated with prednisolone (PSL).…”
Section: Reminder Of Important Clinical Lessonmentioning
confidence: 83%
“…Gastrointestinal symptoms were frequently observed in children with HSP, accounting for 50%~75% [2,3,9], abdominal distention and abdominal pain are the usual clinical manifestations, and the pathological manifestations are erosion, edema and necrosis of gastrointestinal tract mucosa [10]. Typical endoscopic manifestations of HSP include diffuse mucosal edema, erythema and ecchymosis, or multiple irregular ulcers [11,12]. In our study, we found 11 of the 10791 HSP children developed GP, with an incidence of 0.10%, lower than that reported in the literature of 0.38% [13].…”
Section: Discussionmentioning
confidence: 99%